A prospective pilot study to assess neoadjuvant chemotherapy for unresectable peritoneal carcinomatosis from colorectal cancer. (August 2014) - Hompes, D.; Aalbers, A.; Boot, H.; van Velthuysen, M.‐L.; Vogel, W.; Prevoo, W.; van Tinteren, H.; Verwaal, V.
Abstract Aim Twelve to 13% of patients with colorectal cancer (CRC) develop peritoneal carcinomatosis (PC), the majority of whom present with unresectable disease. This study aimed to document the actual response rate to and response characteristics of preoperative modern systemic chemotherapy in this patient group. Method Patients underwent a positron emission tomography (PET)/CT scan, laparoscopy and peritoneal biopsy to document unresectable PC. After four courses of preoperative chemotherapy (capecitabine/oxaliplatin ± bevacizumab), the extent of PC was re‐evaluated by PET/CT(or CT), laparoscopy and peritoneal biopsy (if considered safe). Results Ten patients (seven men, three women) with good performance status of median age 60.3 (45.6–72.8) years were studied. The first laparoscopy documented unresectable PC. One patient was excluded because of systemic metastases on PET/CT. Nine proceeded to follow the trial protocol. Of these, one developed early progressive disease, two had macroscopically stable disease and five had progressive disease at second laparoscopy. One patient developed a small bowel perforation at first laparoscopy and received palliative chemotherapy outside the protocol, after which progressive disease was found at an explorative laparotomy. Thus, 7 (78%) patients with unresectable PC from CRC developed progressive disease under neoadjuvant chemotherapy and 2 (22%) patients remained stable. No clear macroscopic response to chemotherapy could be demonstrated. Conclusion Unresectable PC from CRC does not respond well to systemic chemotherapy.